Serum Total Bile Acids in Relation to Gastrointestinal Cancer Risk: A Retrospective Study - Li, Songbo; Qu, Xiaodong; Zhang, Luyao; Wang, Na; Chen, Min; Zhao, Xingyu; Wang, Jie; Lv, Huanhuan; Qi, Ying; Zhang, Lifeng; Liu, Junye; Shi, Yongquan (Frontiers in Oncology, 2022)
Background: Bile acids (BAs) have been proposed to promote gastrointestinal cells carcinogenesis. However, studies on serum total bile acid (TBA) levels and gastrointestinal cancers (GICs) risk are rare. Methods: We conducted a retrospective case–control study from 2015 to 2019 at the First Affiliated Hospital of Air Force Military Medical University, in which 4,256 GICs cases and 1,333 controls were recruited. Patients' demographic, clinical and laboratory data were collected. The odds ratios (ORs) with 95% confidence intervals (CIs) were estimated using binary logistic regression models. Results: Positive associations were observed between serum TBA levels and risks of esophageal cancer (EC), gastric cancer (GC) and colorectal cancer (CRC). Overall, ORs of EC, GC and CRC risk rose with the TBA levels increasing. After adjustment for potential confounders, the OR of TBA-positive for EC risk was 4.89 (95% CI: 3.20-7.49), followed by GC (OR: 3.92, 95% CI: 2.53-6.08), and CRC (OR: 3.32, 95% CI: 2.04-5.11). Patients aged 60 years or older have a higher risk of GICs, especially for EC patients. Males are associated with a higher risk of GC, while females are associated with a higher risk of CRC. Preoperative serum TBA positive and negative was significantly different in the presence or absence of hematogenous metastasis among EC patients (P=0.014), and lymph node metastasis among GC patients (P=0.018). Conclusions: This retrospective study showed positive associations between serum TBA level and GICs risk, and a higher serum TBA level constitutes a risk factor for GICs.